EFFECT OF SEASON ON METABOLITES AND SEMEN TRAITS OF BULLS - F. G. AL-Gebouri; S. M. Eidan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted to investigate the effect of the winter and spring seasons on some biomarkers and semen characteristics of Holstein bulls (n = 20) during the Coronavirus pandemic period. Semen was collected for 16 weeks and evaluated weekly, along with the determination of some biomarkers. Sperm concentration, live sperm percentage, the concentrations of the most amino acids, essential, non-essential, and total amino acids, all carboxylic acids, omega 3, 6, 9, total fatty acids, and total saturated and unsaturated fatty acids, increased (P<0.05) in semen of spring compared to the winter season. Moreover, the percentage of plasma membrane integrity was higher in the winter than the spring season. The concentration of malondialdehyde in semen decreased (P<0.05) in the semen during the winter compared to the spring season. These biomarkers may have played a role in the fertility and semen quality or were affected by the season and repercussions of the Corona pandemic (feed shortage stress). In conclusion, the level of some amino and carboxylic acids can be adopted as an indicator of climate change (season) and semen quality of bulls or energy level in the diet.